The Contribution of Facilitation Techniques to Proximal Head Control as an Influencing Factor of Postural Control in a Peripheral Vestibular Injury: a Case Report - Martins Felício, João Carlos (Brazilian Journal of Case Reports, 2022)
The Vestibular injury associated with the Peripheral Nervous System is a pathology that causes various alterations in individuals by the absence of afferent information. It mainly affects the orientation of the head and its relationship to the trunk of the body, influencing the individual’s stability by a deficit in balance and coordination. In this context a 69-year-old female subject who had undergone surgery to remove a Schwannoma from the right VIII cranial nerve or Vestibular Schwannoma, with changes in head position and postural control in seated and bipedal positions and also in gait pattern, was evaluated. After a 10-week intervention program (1-hour sessions 2 to 3 times a week) which facilitation techniques based on the Bobath Concept were used, there was a considerable improvement in the subject’s motor and functional status. The subject acquired the cervical rectification strategies necessary for better head alignment, better postural control, and a consequently greater autonomy in walking and daily activities.